2007
DOI: 10.1270/jsbbs.57.123
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Mosaic Virus Resistance in Transgenic Soybean Caused by Post-transcriptional Gene Silencing

Abstract: Somatic embryos of Glycine max (L.) Merrill cultivar 'Jack' were co-transformed with the coat protein (CP) gene of attenuated isolates of Soybean mosaic virus (SMV) and hygromycin phosphotransferase gene by microprojectile bombardment. CP gene was detected in eleven transgenic plants, and three independent lines highly resistant to SMV were obtained in a previous study. One of these lines, line No. 55, which was assumed to have acquired RNA-mediated resistance, was selected for further gene expression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The approach of creating the RNAi structure from the viral CP gene was mentioned by Furutani et al (2007) as an effective method to improve SMV resistance in soybean. However, in reality, soybean plants can be infected with multiple viruses simultaneously; thus, it is important to construct a transgene that can prevent both viruses causing mosaic disease.…”
Section: The Analytic Results From Viral Quantitative Assays By Real-tmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach of creating the RNAi structure from the viral CP gene was mentioned by Furutani et al (2007) as an effective method to improve SMV resistance in soybean. However, in reality, soybean plants can be infected with multiple viruses simultaneously; thus, it is important to construct a transgene that can prevent both viruses causing mosaic disease.…”
Section: The Analytic Results From Viral Quantitative Assays By Real-tmentioning
confidence: 99%
“…In 2007, using the RNAi approach, Bonfim et al obtained a transgenic soybean line with high resistance to Bean golden mosaic virus (up to 93%). Another study (Furutani et al 2007) also tried to improve SMV resistance in soybean using genetic engineering techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, long time (more than 1 year) is needed to obtain transformed soybeans (Furutani 2007;Tougou 2009). Several reports also showed that co-suppression by overexpression of a transgene were reset during the reproduction in several transgenic plants, including soybean plants (Aida and Shibata 1998;Furutani et al 2007;Mitsuhara et al 2002;Yamagishi et al 2006b). Thus, co-suppression by transgene overexpression may not be used for functional analysis of the genes expressed in seed development and early growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the transgenic plants in which a virus-derived sequence is silenced can be resistant to virus infections (English et al 1997). The higher degrees of resistance correlate to lower levels of accumulation of transgenic transcripts and higher levels of siRNA products (Furutani et al 2007;Wu et al 2009). The expression of siRNA is a hallmark of the activated RNA silencing process (Hamilton and Baulcombe 1999).…”
Section: Introductionmentioning
confidence: 99%